Psychopathology of psychiatric patients presenting autoantibodies against neuroglial antigens - Grenzer, Insa Maria; Juhl, Aaron Levin; Teegen, Bianca; Fitzner, Dirk; Wiltfang, Jens; Hansen, Niels (Frontiers in Psychiatry, 2022)
Background Autoantibody-mediated psychiatric disorder is often difficult to diagnose as the clinical features of psychiatric disorder associated with neural autoantibodies are often similar. Thus, it is of major relevance to investigate whether psychopathology can differentiate between both disease entities as a biomarker and help us in searching for specific autoantibodies associated with psychiatric symptoms. Methods We enrolled 154 patients of the Department of Psychiatry and Psychotherapy of the University Medical Center Göttingen with psychopathology data and retrospectively evaluated their patient records using the classification systems AMDP (Arbeitsgemeinschaft für Methodik und Dokumentation in der Psychiatrie) and HiTOP (Hierarchical Taxonomy of Psychopathology). Results We identified 35 psychiatric patients revealing autoantibodies in their serum and/or cerebrospinal fluid (CSF) and 119 with no autoantibodies. Relying on the AMDP system, many more psychiatric patients with serum autoantibodies (51%) had problems with orientation than those without autoantibodies (32%) (p<0.05). Furthermore, fewer psychiatric patients with serum autoantibodies exhibited a blunted affect (11.4% vs 32.8%, p<0.01) and affective rigidity (20% vs. 45%, p<0.01). In particular, psychiatric patients presenting CSF autoantibodies (indicating an autoimmune symptomatic basis) experience more loss of vitality (5%) than those without autoantibodies (0%) (p<0.05). Another interesting finding is that according to the AMDP classification, a manic syndrome is much more frequent in autoantibody-positive (8.6%) than autoantibody-negative psychiatric patients (0.8%) (p<0.05). Another aspect is the more frequent occurrence of attention and memory deficits in patients with autoantibodies against intracellular targets compared with targets on the membrane surface. Conclusions Our findings indicate that neural autoantibodies in psychiatric patients could indicate a phenotype more often characterized by a manic syndrome, orientation disturbances within the cognitive spectrum, and fewer affect disturbances characterized by less blunted affect and not as seriously impaired feelings of vitality compared to controls. The novelty of our approach is the extensive autoantibody tests for various psychiatric syndromes in combination with a profound psychometric measurement with two different scales.